The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1364/boe.10.006258
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of optical attenuation coefficient estimated using optical coherence tomography with changes in astrocytes and neurons in a chronic photothrombosis stroke model

Abstract: The optical attenuation coefficient (OAC) estimated using optical coherence tomography (OAC-OCT) offers a label-free 3D mapping of tissue infarction, but the physiological origin of the OAC contrast remains unclear. For effectively suppressing OAC fluctuations, we propose a hybrid (wavelength/angle) division multiplexing (HDM) method, which improved the OAC contrast by 70.7% in tissue phantoms. To test the feasibility of OAC-based infarction detection, triphenyltetrazolium chloride (TTC) staining was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Based on infarct size, testing within 48–72 h showed better effects compared with that done at hyperacute stage and 4–7 days. On the other hand, previous studies by our group have revealed that loss of blood flow and nervous tissue damage to the ischemic area increased and reached the most at about 3 days after stroke in the rat models, then gradually recovered with recanalization and collateral revascularization 42,47 . The almost coincidence of the two time points indicates that RIPostC has a much prominent efficacy on severe injuries, more importantly, the measurement based on infarct size should be done in the early acute stage to more realistically reflect the therapeutic outcome.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Based on infarct size, testing within 48–72 h showed better effects compared with that done at hyperacute stage and 4–7 days. On the other hand, previous studies by our group have revealed that loss of blood flow and nervous tissue damage to the ischemic area increased and reached the most at about 3 days after stroke in the rat models, then gradually recovered with recanalization and collateral revascularization 42,47 . The almost coincidence of the two time points indicates that RIPostC has a much prominent efficacy on severe injuries, more importantly, the measurement based on infarct size should be done in the early acute stage to more realistically reflect the therapeutic outcome.…”
Section: Discussionmentioning
confidence: 88%
“…reached the most at about 3 days after stroke in the rat models, then gradually recovered with recanalization and collateral revascularization. 42,47 The almost coincidence of the two time points…”
Section: Ta B L E 3 (Continued)mentioning
confidence: 94%
“…These neuroimaging techniques are widely used in clinical settings to diagnose ischemia, but the static nature in both modalities, low sensitivity of CT, and long acquisition time in MRI might affect continuous monitoring of animal ischemic stroke model [23] , [24] , [25] . To overcome these shortcomings, optical coherence tomography has been implemented as a non-invasive method for the dynamic imaging of photothrombotic models [26] , [27] . However, it only provides morphology-based structural details, which is insufficient to obtain blood vessel-based dynamic information.…”
Section: Introductionmentioning
confidence: 99%